(untitled) (Research, Society and Development, 2023)
Smoking is the main cause of death worldwide and is associated with a number of diseases, becoming a public health problem. The objective of this study was to describe the consumption of tobacco in a riverside population of the Bailique/Amapá Archipelago followed-up during a health expedition in the year 2020. Cross-sectional study carried out with 98 participants residing in the Bailique/Amapá Archipelago. Questionnaires with open and closed questions about smoking and the Fagerström Nicotine Dependence Test with descriptive data analysis were applied. Most of the study participants were female and 53.06% said they did not smoke. Ages of initiation of smoking from 15 to 20 years, schooling less than 8 years, and the male sex predominated among the participants who used tobacco. Most participants with lower income never smoked or were former smokers. No one of the participants informed to have a high or very high level of dependence in the self-assessment. It is necessary to invest in health actions aimed at the young single public in order to prevent smoking and its harmful effects.